Manajemen Isu dan Opini Publik dalam Menangani Krisis Reputasi Lembaga Pendidikan - Fatimah J. Harsono; Fidia Laode Hamu; Sulis Maryati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Reputation is a strategic asset that determines the level of public trust in educational institutions. In the digital era, information spreads rapidly through mass media and social media, allowing emerging issues to develop into reputational crises if they are not managed appropriately. This article aims to analyze the role of issue management and public opinion in addressing reputational crises in educational institutions. The study employs a library research method by reviewing relevant scholarly journals and literature on public relations management, crisis communication, organizational reputation, and public opinion. The findings indicate that issue management serves as an early detection mechanism for identifying potential problems that may threaten the reputation of educational institutions. Meanwhile, public opinion management plays a crucial role in shaping public perceptions of an institution’s credibility. Communication strategies that are transparent, responsive, and based on two-way communication have proven effective in helping educational institutions manage and recover from reputational crises. Therefore, the integration of issue management and public opinion into the governance of educational institutions is essential for maintaining sustainable public trust.